PELATIHAN FOTO PRODUK DENGAN STUDIO MINI DARI KARDUS DI WARGA RT 02 JAJAR, SURAKARTA - Arif Yulianto (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
Service with the title "Product Photo Training with a Mini Studio from Cardboard at RT 02 Jajar Residents, Surakarta". The aim of the Product Photo Training is to be able to take their own photos of the goods they sell and promote their food or beverages, so as to increase the selling power of their stores during the pandemic. This service is using a descriptive method. Methods of data collection with literature study, observation, and interviews. This training invites women from RT 02, Jajar to take product photos with a mini studio so that their products can be sold. The problem with the RT 02 community is that they don't know what product photos are and how they are used. They don't even understand the use of cell phone cameras to shoot objects with good composition. To answer these problems, training was held on photographing product photos, making hands-on and learning to use a cell phone camera with good composition. The results of this service get good and interesting product photos so that their products can attract public buyers.